The perceived versus actual risk of developing type 2 diabetes mellitus in a New Zealand population : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Human Nutrition at Massey University, Albany, New Zealand - Evans, Elizabeth (Massey University, 2020)
Background: Type 2 diabetes mellitus (T2DM) has been termed one of the fastest growing non–communicable diseases of all time. Recent research estimates the current prevalence rate of T2DM in New Zealand to be 6.4%, representing 210,000 New Zealand adults. However, the prevalence rate for prediabetes; the precursor to T2DM, is estimated to be much higher, at 25.5%. An individual’s awareness of their risk for developing T2DM is essential to mediate change, which is the first step in managing the disease. However, studies have shown a difference between an individual’s actual disease risk and their perceived risk. Aim: To investigate an individual’s perception of risk and compare it to their actual risk of developing T2DM in a New Zealand population. A secondary aim is to investigate determinants of perceived risk in developing T2DM. Methods: 257 New Zealanders over the age of 18 years, nonpregnant and not diagnosed with diabetes (type 1 or 2) were recruited for this study. Eligible participants took part in an anonymous 10–minute online questionnaire, to assess perceived risk using a validated Risk Perception Survey for Diabetes Development (RPS–DD) and actual risk of developing T2DM using the Diabetes New Zealand ‘Are you at risk?’ calculator. Statistical analysis via SPSS version 26 was performed to test for differences between low and high perceived risk groups. Regression analysis was conducted to investigate determinants that predict the probability of perceived risk in developing T2DM. Results: Fifty–three percent (135/257) of participants had an increased actual risk (New Zealand Diabetes ‘Are you at risk?’ score >5) of developing T2DM, however 86% (220/257) of participants perceived their risk of developing diabetes to be low. Significant differences between participants with low perceived versus high perceived risk were observed for; GP–recommended testing for CVD/T2DM (56% v 78%, P=0.02), GP communication about CVD/T2DM risk (24% v 51%, P<0.001), prediabetes diagnosis (4% v 24%, P<0.001) and BMI (kg/m2) (24 (22.1, 26.4) v 27.4 (25.3, 30.8) P<0.001). Significant predictor variables of the logistic regression model included; prediabetes (OR 8.97 (95% CI 1.61–50.10), P<0.01), eating a diet high in fat and sugar (OR 6.29 (95% CI 1.83–21.63), P<0.01), family history of T2DM (OR 10.17 (95% CI 3.0 – 34.47), P<0.001), low comparative disease risk (OR 0.05 (95% CI 0.01 – 0.18), P<0.001) and planned lifestyle modifications to reduce risk of T2DM (OR 7.13 (95% CI 2.05 – 24.85), P=0.002). Conclusion: This study demonstrates that a participant’s perceived risk of developing T2DM significantly underestimates their actual risk in 257 participants from a New Zealand population. While prediabetes and BMI have been well established in the literature for their association with increased risk perception of developing T2DM, the role of GP–based communication has not. Further research is needed to explore GP–based communication, and the potential impact this has on an individual’s understanding of risk in developing T2DM.
Keywords: prediabetes; risk perception; type 2 diabetes mellitus; Risk Perception Survey of Diabetes Development (RPS-DD); risk communication; GP communication; 321004 Nutritional science